FPGA-Based Synchronization of Frequency-Domain Interferometer for QKD - Nishanth Chandra; Pradeep Kumar Krishnamurthy (IEEE Transactions on Quantum Engineering)
In this article, we propose and experimentally demonstrate a novel synchronization method for quantum key distribution (QKD) systems. The method consists of maximizing the visibility of frequency-domain interference of optical sidebands about an optical carrier at the receiver node. The sidebands are generated by phase modulation of the optical carrier by an radio-frequency (RF) signal whose phase can be dynamically varied. The phase-variable RF signal is generated by the field-programmable gate array (FPGA) at the transmitter and the receiver using GTX transceivers. In order to facilitate this, we use square waveforms for RF signal instead of the conventional sinusoidal signals. We derive mathematical expressions for sideband power as a function of the phase difference between RF signals at transmitter and receiver. The phase is adjusted using dynamic phase shifter module, implemented by the FPGA. We propose a complete workflow that allows transmitter and receiver synchronization to within 12.6 ps directly over the quantum channel of QKD systems. Once synchronized, the same system can be switched over to quantum transmission by user-defined time delay. The workflow was implemented on a Xilinx Kintex-7 KC705 FPGA board. We studied the robustness of our technique by evaluating the stability of the interferometer over an operation of 10 min with standard deviation of interference to be less than 9% of the mean detection amplitude.